Collisions of adjusting of separate rights for a patient at grant of medicare - Оніщенко, Ольга Вікторовна; Сорока, Галина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is dedicated to analysis of some legislative inaccuracies in the context of the right to health care, right to refuse health care; views of scientists and draft legislation are analyzed regarding on «rights of patient» expression and basis of classification of patients’ rights.